Strategi Sekolah Dikdasmen Kabupaten Kendal dalam Menghadapi Pembelajaran di Era New Normal - Irkham Ulil Albab; Yanuar Hery Murtianto; Aryan Eka Prastya Nugraha; Sumarno Sumarno (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Facing learning in the New Normal era, teachers must be able to prepare creative and innovative learning that is not just giving online assignments. However, during the pandemic, teachers have problems when carrying out learning. Most teachers find it difficult to prepare creative online learning materials. As a result, learning is ineffective, there is no interaction between students, and tends to the division of tasks. The PGRI Semarang university service team offers solutions in the form of learning strategies by combining the themes of each lesson so that learning can be carried out effectively through STEAM-based learning. The use of telegrams for interactive quizzes and Porprofs as a comprehensive evaluation tool that makes it easier for teachers is one of the solutions in learning in the new normal era.